INCIDENCE OF CHRONIC MYELOPROLIFERATIVE DISORDERS IN UZBEKISTAN - Jakhonov Azizbek Kholmirzaevich; Matkarimova Dilfuza Saburovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Chronic myeloproliferative disorders (CMPDs) are a group of clonal hematopoietic stem cell diseases characterized by persistent proliferation of myeloid cell lineages in the bone marrow and peripheral blood. This group includes chronic myeloid leukemia, polycythemia vera, essential thrombocythemia, and primary myelofibrosis. The present study analyzes the incidence, epidemiological characteristics, and regional distribution of chronic myeloproliferative disorders in the Republic of Uzbekistan. The research is based on a retrospective analysis of available national publications and statistical reports. The results demonstrate that CMPDs are relatively rare in Uzbekistan; however, an increasing trend in detection has been observed in recent years, likely due to improvements in diagnostic methods and hematological services.